International Terrorism and the Middle East: An Expository Approach - Ibietan, PhD, Jide; Chidozie, PhD, Felix; Ujara, Ese (Covenant University Journal of Politics and International Affairs, 2016)
This paper interrogates the role of the Middle East in international terrorism and the spillovers of this on global security. The narrative traces the roots of terrorism to the Middle East, noting the volatility of the issue and susceptibility of some countries within that region to terrorism, zeroing-in on Iran as misconstruing this vice for foreign policy instrument. Essentially, the paper relied on secondary data, statistical tools backed by the analytical approach, leading to the inference that the terrorist network and activities have wider international ramifications and reverberating effects on developing countries, including Nigeria. The adoption of more proactive measures and pragmatic security-building strategies by the United Nations towards a deceleration in international terrorism were canvassed.